DEVELOPMENT OF STUDENTS’ LEARNING AND RESEARCH SKILLS ON THE BASIS OF PHYSICAL EXPERIMENTS - Kusharbay Tashbayevich Suyarov (Web of Journals Publishing, 2023)
This article deals with the methods of teaching physics on the basis of physical experiments. The models of the methodological system for the development of teaching and research skills of general education school students are given, and the results of the experiments are also presented.
Keywords: Educational-research work, educational-research skills, creative thinking, methodological system, physical experiment.